A light-emitting-diode pulsing system for measurement of time-resolved luminescence - Uriri, Solomon Akpore (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2015)
A new light-emitting-diode based pulsing system for measurement of time-resolved luminescence has been developed. The light-emitting-diodes are pulsed at various pulse-widths by a 555-timer operated as a monostable multivibrator. The light-emitting-diodes are arranged in a dural holder connected in parallel in sets of four, each containing four diodes in series. The output pulse from the 555-timer is fed into an 2N7000 MOSFET to produce a pulse-current of 500 mA to drive the set of 16 light-emitting-diodes. This size of current is sufficient to drive the diodes with each driven at a pulse-current of 90 mA with a possible maximum of 110 mA per diode. A multichannel scaler is used to trigger the pulsing system and to record data at selectable dwell times. The system is capable of generating pulse-widths in the range of microseconds upwards.
Keywords: Uncatalogued